Tutor Competence in Realizing the Success of Japanese Language Training Participants (Case Study at LPK Proklamator Padang) - Amelia, Putri; Putri, Lili Dasa (Universitas Negeri Padang, 2024)
This research is motivated by the unique phenomenon in Japanese language training at LPK Proclamator, which is the number of training participants who graduated and participated At LPK Proclamator. This is influenced by the competence of a tutor. This study aims to determine the tutor's competence in Japanese language training at Padang Proclamator LPK.This study uses a qualitative approach, with a case study research method. The data sources in this study are managers, tutors, Japanese language training participants. Data collection techniques conducted in this study are observations, interviews and documentation. Data analysis techniques used are data reduction, data presentation and drawing conclusions. Data validity techniques are by using source triangulation, triangulation of theoretical methods and triangulation.The results of the research show that (1) The pedagogical competence of LPK proclaimer tutors is mastering the characteristics of training participants, mastering learning theory and principles of educational learning, developing a curriculum related to Japanese language training, organizing an educational learning process, utilizing information and communication for the benefit of learning, facilitating the development of the potential of training participants to actualize the various potentials they have as well as carrying out assessments and evaluations of the learning process and results. (2) Personality competency of the LPK proclaimer tutor to act in accordance with the rules, presenting oneself as an honest, wise person and displaying an authoritative personality. (3) The social competence of proclaimer LPK tutors is to be non-discriminatory, communicate effectively, empathetically and politely with fellow educators, education staff, parents and the community in the environment, and adapt to the environment where they work in order to increase their effectiveness as educators. (4) The professional competency of the Proclaimer LPK tutor is to master the material, learning objectives, structure, learning concepts and develop creative learning materials in Japanese language training at the Proclaimer LPK.Keywords: Tutor Competency, Training, LPK